Business risk management : models and analysis - Anderson, E. J. (Edward J.), 1954-; Wiley eBooks (Chichester, West Sussex, UK : Wiley, 2014)
"Providing the foundations needed for managers who have to make decisions in an uncertain and risky environment, Business Risk Management brings together the fundamental ideas of utility theory and at the same time puts them alongside prospect theory which describes how people actually make decisions on risk using quantitative tools and probability models to provide a clear understanding of risk. Author Edward Anderson examines an ambitious range of topics, introducing practically important concepts in a way that does not require an advanced understanding of financial mathematics"--
"Business Risk Management provides the foundations needed for managers who have to make decisions in an uncertain and risky environment, using quantitative tools and probability models to provide a clear understanding of risk"--
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Risk management; MATHEMATICS / Probability & Statistics / General; Risk management; Electronic books